Post traumatic facial nerve palsy without temporal bone fracture. Issue 1 (February 2016) - Scuotto, A.; Cappabianca, S.; Capasso, R.; Porto, A.; D'Oria, S.; Rotondo, M.
Abstract: Facial nerve injury following head trauma is a frequent event with or without temporal bone fractures. Computed tomography is the imaging modality of choice for assessing the possible bone disruption of the facial nerve canal. Magnetic resonance is helpful in presence of a facial nerve paralysis, unexplained by computed tomography findings. We present a case of delayed post-traumatic facial nerve palsy without radiological evidence of temporal bone fractures, in which magnetic resonance was crucial for diagnosing the nerve impairment. Radiological findings in accordance both with electrodiagnostic tests and clinical presentation suggested the successful conservative management. Highlights: Facial nerve is more prone to damage than any other cranial nerve after trauma. Facial nerve trauma is usually associated with temporal bone fractures. MRI is mandatory in case of no evidence of bone disruption at CT.